Genotype-nitrogen-environment interaction and stability of blast resistant rice in multi locational trials - Almu, Hamisu (2019)
Rice shortages have become a serious problem due to high demand as a result of increasing world population. To meet the global rice demand by 2030, its production needs to be increased by more than 50% worldwide. In Malaysia, the average rice production of 4.2 t/ha is considered as low largely due to insufficient nutrients and blast disease. The main objective of this study was to identify high yielding, blast resistant and highly stable rice genotypes with high nitrogen efficiency for commercial cultivation in Malaysia. Sixteen blast-resistant rice genotypes were evaluated in three rice granary areas (Tanjung Karang, Selangor; Kota Sarang Semut, Kedah and Seberang Perai, Penang) with five different nitrogen fertilizer levels over two planting seasons (Main and off seasons). Five nitrogen fertilizer levels:- 60, 80, 100, 120 (standard recommendation) and 140 kg N/ha were applied in each location and planting season. The experimental design was a split plot design with three replications, where the nitrogen fertilizer levels was assigned as main plot and rice genotypes as sub-plot. Nitrogen levels had highly significant effects on all the yields and vegetative traits except, panicle length, grain length and grain width. There was also presence of interaction between genotype and nitrogen levels in all the environments on all traits except, number of tillers per hill, number of panicles per hill and filled grain per panicle. In addition, the genotype by nitrogen interaction was highly significant for all traits except unfilled grain per panicle, panicle length, grain length, grain width and yield per hectare. The nitrogen yield efficiency differed significantly with various levels of nitrogen applied. The optimum nitrogen levels for MADA, Seberang Perai and Tanjung Karang were 112, 125 and 105 kg N/ha with yield production of 9.53, 8.99 and 9.48 t/ha, respectively. The results revealed that the ideal environment were ENV6 (Seberang Perai 2), ENV 2 (Tanjung Karang 1) and ENV4 (MADA 2). From the result obtained on stability analyses, two genotypes (Genotype 9 and 16) were found to be highly stable across the environments and produced high yield with 9.39 and 9.13 t/ha, respectively. However, the agronomic nitrogen yield efficiency across environments for the two genotypes were 6.23% and 2.79%, respectively, at 140 kg N/ha. The two superior genotypes (Genotype 9 and 16) with high yield and stability across environments are recommended for commercial cultivation in Malaysia.